2016
DOI: 10.18533/ijbsr.v6i9.985
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic and Intrinsic Factors Influencing Employee Motivation: Lessons from AMREF Health Africa in Kenya

Abstract: The purpose of the study was to determine the factors that influence employee motivation in Kenyan Organizations. The study was guided by the following research questions: (i) what are the extrinsic factors that influence employee motivation in AMREF Health Africa in Kenya? (ii) what intrinsic factors influence employee motivation in AMREF Health Africa in Kenya? A descriptive research design was adopted. Stratified random sampling technique was used to draw a sample size of 96 respondents. The data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
2
7
0
1
Order By: Relevance
“…This study revealed that health extension workers who received stimulating recognition from management were more satisfied with their job compared to their counterparts. This finding was in line with studies carried out in East Shewa Zone of Oromia Region, 33 Harar City, 26 West Ethiopia, 35 and Northern Ethiopia, 37 public health facilities of Ethiopia, 29 Kenya, 41 Eastern Cape, 42 and Iran. 43 This could be explained as recognition has the potential to motivate the HEWs, enhance their skills, create a good attitude toward achieving the common organizational goal, and finally make HEWs more likely satisfied.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study revealed that health extension workers who received stimulating recognition from management were more satisfied with their job compared to their counterparts. This finding was in line with studies carried out in East Shewa Zone of Oromia Region, 33 Harar City, 26 West Ethiopia, 35 and Northern Ethiopia, 37 public health facilities of Ethiopia, 29 Kenya, 41 Eastern Cape, 42 and Iran. 43 This could be explained as recognition has the potential to motivate the HEWs, enhance their skills, create a good attitude toward achieving the common organizational goal, and finally make HEWs more likely satisfied.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, rural health extension workers who got adequate supportive supervision in their work were more likely to be satisfied as compared to their counterparts. This finding is in line with studies done in the East Shewa Zone of Oromia Region, 33 Northeast Ethiopia, 37 Gambella Region, 18 Kenya, 41 and, Nigeria. 34 This could be explained by the fact that adequate and effective supportive supervision can motivate HEWs leading to satisfaction on their job.…”
Section: Discussionsupporting
confidence: 91%
“…The effect of motivation on perceived performance demonstrated in the present study is consistent with previous research [ 37 , 75 , 79 , 80 ]. Nyambegera and Gichery [ 106 ] reported that intrinsic motivation affects improvement in work skills. However, our results confirmed that work skills are stimulated by extrinsic motivation, which is supported by prior research [ 37 , 45 , 46 , 47 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The items used are found in Appendix A. Motivation was evaluated by 24 items validated by (Bao & Nizam, 2015;Nyambegera & Gicheru, 2016), organization commitment was assessed by 19 items validated by (Irefin & Mechanic, 2014;Tolentino & Ng Lungsod Ng Maynila, 2013), delegation authority was measured by 16 items validated by (Al-Jammal, I., Al-Khasawneh, J.A & Hamadat, 2015), employees' performance was assessed by 15 items validated by (Gohari, Ahmadloo, Boroujeni & Hosseinipour, 2013).…”
Section: Methodsmentioning
confidence: 99%